Fonte Grande Park & Gruta da Onça in Vitória - ES: history, preservation and conservation - Nemer, Luciana (National Journal of City Management, 2023)
The paper presents the history of Parque da Fonte Grande and Gruta da Onça in Vitória, state of Espírito Santo, reporting their stories, creations, preservation and conservation actions. The research reaches the present day describing its uses and purposes. The text also discusses how the creation process of the National Parks took place. In the methodology, queries in secondary sources stand out (books, book chapters and course completion works), municipal and federal documents were also examined, in addition to iconographic and cartographic research carried out in the Municipal Archive of Vitória and also field trips with interviews. The results describe the evolution of both, their functions, interventions and participation in the life of the city. The conclusions highlight how much the parks, as geographic elements, attributed challenges, scenic beauty and awakened the population and the state and municipal governments for environmental education actions, appreciation and preservation of the natural landscape heritage.